Synergistic torrefaction and co-combustion of rice husk and spent coffee grounds: Thermo-kinetics, ash morphology, and waste-to-energy implications - Pambudi, Suluh; Jongyingcharoen, Jiraporn Sripinyowanich; Saechua, Wanphut (My University, 2026)
Combining silica-rich agricultural residues such as rice husk (RH) with energy-dense food-processing waste like torrefied spent coffee grounds (TSCG) offers a circular strategy to exploit the complementary advantages of each biomass while improving fuel performance and combustion reliability. Therefore, the objective of this study is to systematically investigate the co-combustion behavior, kinetic performance, and ash morphology of RH and TSCG blends using thermogravimetric analysis across multiple blend ratios and heating rates. Optimal co-combustion characteristics were observed for blends containing 40–60% RH, demonstrated by comprehensive combustion index values up to 6.02 × 10–6%2 min–2 °C–3 and flammability indices exceeding 0.72 × 10–4% min–1 °C–2. Furthermore, these blends exhibited low activation energies during dehydration (150–161 kJ mol⁻¹), devolatilization (143–175 kJ mol⁻¹), and char oxidation (89–134 kJ mol⁻¹). Notably, these blends exhibit high carbon conversion efficiency, leading to a relatively low residual ash content (10.25–14.36%). Synergistic effects, characterized by experimental mass loss exceeding theoretical predictions by up to 2%, were confirmed above 300 °C. This synergistic behavior is attributed to the interaction between oxygenated volatiles released from RH and the catalytic effects of alkali and alkaline earth metals present in TSCG, along with the stabilizing role of silica in mitigating ash-related issues. Additionally, increasing the proportion of TSCG promoted earlier ignition (Ti reduced to 213 °C) but prolonged the char combustion stage, resulting in higher burnout temperatures of up to 678 °C. Morphological and elemental ash analysis revealed that moderate Si content in 40–60% RH blends contributed to thermal stability while suppressing alkali-induced slag formation. Collectively, these results demonstrate that co-combustion of RH with TSCG significantly enhances combustion reactivity, promotes kinetic synergy, and improves thermal stability. These findings highlight the potential of RH–TSCG blends as efficient and environmentally sustainable fuels for bioenergy applications by utilizing readily available local biomass residues.
Keywords: Ash characteristics; Co-combustion; Combustion kinetics; Rice husk; Torrefied spent coffee grounds